PENGARUH EARNING PER SHARE, RETURN ON EQUITY, DAN DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM PERUSAHAAN SUBSEKTOR PERKEBUNAN DI BURSA EFEK INDONESIA TAHUN 2014-2018 - Sudarlan Sudarlan; Muhammad Suyudi; Muhammad Sainudin Noor (Politeknik Negeri Samarinda, 2020)
This research aim to help investors in deciding to invest in the stock market by analyzing the impact of company’s financial ratio on its share price. Finacial ratio used in this research are Earning per Share, Return on Equity, and Debt to Equity Ratio as independent variables, and Stock Price as the dependent variable. The method used in this reseach is purposive sampling with population is 18 plantation companies and sample is 10 companies. Data were tested using the classical asumptiont and multiple linear regression used SPSS 25. The result of this research shown that ROE does not effect significantly to company’s stock price. And EPS effect positif and significantly, and DER effect negatif and significantly to company’s stock price. From F test’s result shown that EPS, ROE, and DER together effect significantly to company’s stock price. Keywords: Earning per Share, Return on Equity, Debt to Equity Ratio, Stock Price.